"Life's too short to be small": An experimental exploration of the relationship between death anxiety and muscle dysmorphia symptoms. (March 2023) - Menzies, Rachel E.; Sharpe, Louise; Richmond, Bethany; Cunningham, Mitchell L.
Abstract: Growing research demonstrates that death anxiety is strongly associated with numerous mental health conditions. It is possible that death anxiety may similarly contribute to behaviours associated with muscle dysmorphia (MD). The current pre-registered study examined this possibility in 322 young men with an interest in health and fitness. The mortality salience paradigm was used to experimentally examine whether reminders of death increased behaviours relevant to MD. Measures of MD symptoms and death anxiety were also completed by participants. Contrary to expectations, reminders of death did not significantly increase willingness to trial workout supplements, or dissatisfaction with current muscularity. Participants reminded of death reported lower intention to exercise in the near future, compared to the control condition. Moreover, death reminders did not lead to significantly larger portion sizes being chosen. However, in post-hoc analyses, men with high, but not low, MD symptoms did choose larger portions after being primed with death. Lastly, positive correlations were found between self-report measures of MD symptoms and two measures of death anxiety. Cumulatively, these results suggest that while fears of death may be associated with self-reported MD symptoms, they may not drive excessive exercise, nor body dissatisfaction in men. Highlights: Death anxiety has been shown to play a causal role in numerous mental disorders. The current study explored the role of death anxiety in muscle dysmorphia (MD). Death anxiety was positively correlated with MD symptoms. Reminders of death did not increase exercise intention or body dissatisfaction. Death reminders did increase portion size selected among men with high MD symptoms.